THE RELATIONSHIP BETWEEN PSYCHOLOGICAL WELL BEING AND QUARTER LIFE CRISIS IN FRESH GRADUATE UNIVERSITY OF MUHAMMADIYAH SIDOARJO - Rachma, Alsa Nabilah; Nastiti, Dwi (Proceeding of International Conference on Social Science and Humanity, 2025)
being and the quarter-life crisis among fresh graduates of Universitas Muhammadiyah Sidoarjo. Method: A quantitative correlational approach was employed with a sample of 279 respondents, selected using the Issac & Michael table. The Psychological Well-Being scale based on Ryff's theory and the quarter-life crisis scale based on Robbins and Wilner’s aspects were utilized as instruments. Results: The Spearman rho correlation test revealed a very strong inverse correlation between psychological well-being and the quarter-life crisis (r = -0.884; p < 0.001), indicating that higher mental well-being is associated with a reduced likelihood of experiencing a quarter-life crisis. Additionally, determination analysis showed that psychological well-being accounts for 78.1% of the variance in the occurrence of a quarter-life crisis. Novelty: This research contributes to understanding the significant role of psychological well-being in mitigating the challenges faced during the transition from graduation to the workforce, emphasizing the importance of mental health support during university years to prepare graduates for post-graduation challenges.